Comparison Between Endoscopic Sclerotherapy and Band Ligation for Haemostasis of Variceal Bleeding at National Centre for Gastrointestinal and Liver Disease, IbnSina Specialized Hospital – Khartoum - A.Hamoda, Alaeldin; MMusaad, Abdulmagid; Arabi, Nassir A (Gezira Journal of Health Sciences, 2018)
The objective of this hospital-based  and prospective study was to compare the outcome of endoscopic variceal sclerotherapy and band ligation regarding early and late rebleeding. Oesophagealvariceal bleeding is the most common cause of upper gastrointestinal tract haemorrhage. Patients with oesophageal variceal bleeding have higher rates of rebleeding, complications, and death than patients with non-variceal bleeding such as ulcer bleeding (1) . Between the year Dec. 2016 –Apr. 2017 a total of 140 patients were reviewed. Variables selected for the study included: intervention type: whether it was sclerotherapy or banding , OGD findings at presentation, presence of shock upon presentation, duration of having the disease before the intervention and outcome of each procedure . Males were (110) females (40). The Majority of patients presented with hematemesis and melena (74.28  %), hematemesis alone  occurred in (28.57%) and melena alone in ( 7.14%) of patients. All patients were diagnosed as portal hypertension due to PPF (Belharziasis) and most of them were from Gezira State.  Most of the patients  had portal hypertension  for more than two years (41.4%). Sixty patients presented with different stages of shock (42.9%).Sengestaken tube was used to control bleeding in (5%) of patients. On the other hand 79.4% of patients received blood during resuscitation. Regarding OGD findings, nearly all patients were found to have OV alone (97.6). Previously only six patients underwent splenectomy, three between 1-2 years, one before five years and one in less than one year. Of the 140 patients (49.3%) were treated with Sclerotherapy and (50.7%) underwent band ligation. With regard to rebleeding, of those who were treated with Sclerotherapy, (14.49%) of patients rebled early, (26.09%) rebled late, (49.28%) did not rebleed and seven patients lost their follow up. Comparing to Sclerotherapy, re bleeding in band ligation were found early in(15.95%), ( 23.19%) presented as late, (57.97%) did not rebled and two patients lost the follow up.. In conclusion: Treatment of oesophageal variceal bleeding with band ligation has lower rates of re-bleeding. Chronicity of portal hypertension appears to be a significant risk factor for re-bleeding after both procedures.